2004
DOI: 10.1210/jc.2003-031822
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Fasting Serum Radioimmune Insulin Levels to Incident Coronary Heart Disease in an Insulin-Treated Diabetic Cohort

Abstract: It is not known whether insulin levels, in the setting of insulin treatment, are an independent risk factor for coronary heart disease (CHD). We studied a cohort of 116 insulin-treated individuals, 65 yr or older, who were followed for 5.6-9 yr. All were free of CHD at baseline. There were 47 incident CHD events. In Cox proportional hazards modeling, with fasting immune-reactive insulin levels as a continuous variable, the hazard ratio for CHD was statistically significant (P < 0.0001). When insulin levels wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…This finding was also reported in the PROactive cohort of type 2 patients with prior myocardial infarction who developed a second fatal or nonfatal myocardial infarction (4) and in the Cardiovascular Health Study (19), in which insulin was found to be associated with greater CVD mortality compared with oral agents. The association was true also when serum insulin concentrations were measured (20). In the DAI study, insulin treatment was an independent risk factor for IHD (12) and stroke (13) in patients free of CVD at baseline as well.…”
Section: Discussionmentioning
confidence: 84%
“…This finding was also reported in the PROactive cohort of type 2 patients with prior myocardial infarction who developed a second fatal or nonfatal myocardial infarction (4) and in the Cardiovascular Health Study (19), in which insulin was found to be associated with greater CVD mortality compared with oral agents. The association was true also when serum insulin concentrations were measured (20). In the DAI study, insulin treatment was an independent risk factor for IHD (12) and stroke (13) in patients free of CVD at baseline as well.…”
Section: Discussionmentioning
confidence: 84%
“…Most studies showed no relationship between IAs and changes in insulin dose requirements [9]. However, in a recent study, immune-reactive insulin levels were strongly correlated with IA levels, and elevated fasting immunoreactive insulin levels were an independent risk factor for coronary heart disease in insulin-treated older adults [60].…”
Section: Reduced Insulin Action and Risk Of Hyperglycaemiamentioning
confidence: 95%
“…Subsequently, the finding of highest mortality in the tolbutamide-treated group was attributed to reduced ischemic preconditioning seen predominantly, but not exclusively, with first-generation sulfonylureas. 8,9 Increased plasma insulin concentrations have been associated with adverse cardiovascular outcomes, regardless of whether the insulin source is exogenous (ie, administered therapeutically) 10 or endogenous in origin. 11 On the other hand, insulin treatment in both type 1 and type 2 diabetes mellitus has been associated with improved outcomes over the long term.…”
Section: Insulin-provisional Compared With Insulin-sensitization Thermentioning
confidence: 99%